186Re-HEDP: A Potential Therapeutic Bone Agent - Weininger, J.; Ketring, A. R.; Deutsch, E. A. (Nuklearmedizin - NuclearMedicine, 1984)
A lyophilized kit preparation of HEDP for labelling with 186Re has been developed as a potential bone agent useful for both diagnosis and therapy. High pressure liquid chromatographic analysis showed that the 186Re-HEDP is a mixture of several components. Preliminary in vivo studies in several animal species showed that both the 186Re-HEDP mixture and the HPLC-purified main component are bone-seeking agents with slow blood and soft-tissue clearance rates. HPLC purification slightly improved the quality of the image. In mice and rats with trauma-induced osteogenetic activity in one leg, the bone uptake of the traumatized leg was 1.7-1.9 times higher than of the normal leg. The lesion-to-normal bone ratio was 4-5.4.